Effect of temperature and composition of mixed solvent media on the interaction of bromocresol Green dye with cetylpyridinium chloride. (18th July 2021) - Islam, Shakirul M.; Mahbub, Shamim; Ahmad, M. Ayaz; Mustafa, Syed Khalid; Alasmary, Fatmah Ali; Hoque, Md. Anamul
Abstract : The study of dye-surfactant interaction is very important in achieving an optimal dyeing process in textile industries. Conductivity measurements of the cationic surfactant cetylpyridinium chloride (CPC) in the presence of bromocresol green dye (BCG) in various solvents were performed, in order to provide insight into the interaction between BCG and CPC. Three critical micelle concentrations ( cmc ) were observed over the studied CPC concentration range. The observed cmc values of the BCG + CPC system were found to change significantly as a function of BCG concentration. The cmc values of the BCG + CPC system showed U-shaped variation, with increasing temperature in aqueous and propanol media, while decreasing monotonically in ethanol media. The concentration of additives (ethanol, propanol, and propylene glycol) also affected the cmc values significantly. The values of counterion binding (β) were also found to be dependent on the temperature and concentration of additives. Different thermodynamic parameters, e.g. Gibbs free energy ( Δ G m o ), enthalpy ( Δ H m o ), and entropy ( Δ S m o ) changes, as well as their transfer properties associated with micellization of the BCG + CPC system, were determined. The Δ H o m and Δ S o m values reveal the presence of hydrophobic, ion-dipole, or dipole-diploe interactions amongst employed constituents. GRAPHICAL ABSTRACT: UF0001